Combined finite-discrete element modelling of rock fracture and fragmentation induced by contour blasting during tunnelling with high horizontal in-situ stress. (March 2020) - Han, Haoyu; Fukuda, Daisuke; Liu, Hongyuan; Salmi, Ebrahim Fathi; Sellers, Ewan; Liu, Tingjin; Chan, Andrew
Abstract: A combined finite-discrete element method (FDEM) parallelized on the basis of GPGPU is implemented to model the rock fracture and fragmentation process and the resultant excavation damaged zone (EDZ) development induced by the controlled contour blasting, which was conducted in the TASQ tunnel with high in-situ stresses in the Äspö Hard Rock Laboratory in Sweden. The combination of in-situ stress field, equation-of-state based blast loading, fracturing in tension and shear with gas flow loading of fractures enables the modelling of complex dynamic interactions from multiple blast rounds. For the contour blasting under high horizontal in-situ stresses, blasting-induced fractures initially propagate horizontally, even though the holes are decoupled. Later, these fractures coalesce into larger cracks, which prevents the formation of smooth tunnel walls and increases the EDZ. Smoother surfaces are created at the crown and invert by the propagation of long fractures in the horizontal direction. Due to the combined effect of the free surfaces provided by the adjacent blast-holes and the maximum principal stress induced by in-situ stresses, the fractures at the lower part of the tunnel sidewalls have the tendency to propagate upwards with a diagonal direction about 60° relative to vertical, in accordance with the field test results. Removing the in-situ stresses results in smoother sidewall fracturing with more damage in the crown and invert. Increase in rock heterogeneity, above a threshold, induces more fractures. Increasing the detonation timing between blast-holes induces more damage into the rock mass and fragmentation in the burden. Outcomes of this study show that the GPGPU-parallelized Y-HFDEM IDE provides a powerful tool to replicate the mechanisms of rock fracture and fragmentation induced by blasting.